A revisão curricular do curso de licenciatura em história da Universidade Federal do Acre (1996-2005): relações de poder e resistência - Machado, Tânia Mara Rezende (2010)
This work is focused on the analysis of the curriculum reform of the Teaching Degree Course on History of the Federal University of Acre (Ufac) which took place from 1996 to 2005. To accomplish this objective, it prioritizes the review of curriculum official normalization and prescriptions from Ministério da Educação (MEC) (Brazilian Ministry of Education) directed to the organization of bachelor degree courses to teachers in Brazil. This study is based on the bibliography review, sources such as Lei de Diretrizes e Bases da Educação Nacional (Law of Directives and Principles of the Brazilian National Education), Diretrizes Curriculares Nacionais para a Formação Inicial de Professores da Educação Básica (Brazilian National Curriculum Directives for the Graduation Degree of Basic Education Teachers), bachelor course as of 2000, Diretrizes Curriculares Nacionais para o Curso de Graduação em História (Brazilian National Curriculum Directives for the Graduation Course on History) as of 2001 and Ufac internal documentation. It aims at, as a central focus point, identifying how the members of the Academic Course at that time took over the leading role of the process and how power and resistance relations developed among the members of the group. The resistance category is handled from Giroux (1983) point of view which defines it as an intentional human action capable of producing emancipation; on the other hand, the power category is analyzed from the perspective of Apple (1989) studies to whom power consists of how men, based on their cultural and politic actions, create opposite conditions to the control over their works. This investigation intends to contribute to think over the propositions coming from MEC and how they were accepted in the preparation of the Pedagogical Project of the History Teaching Degree Course of Ufac indicating achievements and regressions brought to History teachers graduation in Acre